RELATIONSHIP BETWEEN SEXUAL DYSFUNCTION AND SEXUAL SELF-CONCEPT IN PATIENTS WITH DIABETES MELLITUS: A SCOPING REVIEW - Amalia Mentari, Tiara; Haryanto (Nurse and Health: Jurnal Keperawatan, 2024)
Background: An often-occurring complication of diabetes mellitus is sexual dysfunction, often linked to poor blood sugar control. Despite its significant impact on patients' lives, issues related to sexual desire, education, and timely detection and management of sexual problems have historically been overlooked in diabetes interventions. This neglect may affect individuals' sexual self-concept and overall well-being. The purpose of this study is to investigate the relationship between sexual dysfunction and sexual self-concept in diabetics. Design: This research employs a scoping review design. Data Sources: A comprehensive literature search was conducted using databases such as Web of Science, Open Alex, Crossref, Google Scholar, PubMed, Scopus, and Semantic Scholar. Articles published between January 2018 and October 2023 were included. Review Methods: The analysis followed the Arksey and O'Malley model and PRISMA guidelines. 26 quantitative articles were reviewed, including 24 cross-sectional studies and 2 observational studies, all using quantitative methodologies. Results: Sexual dysfunction is prevalent among diabetes type 1 and type 2 in both men and women, influenced by physiological factors and glycemic control. Men may experience issues like diminished libido, premature ejaculation, and difficulty achieving orgasm, while women may face reduced sexual desire, arousal difficulties, and dyspareunia. Factors contributing to sexual dysfunction include age, duration of diabetes, glycemic control, comorbidities, medication use, psychological factors, and lifestyle elements like physical activity and stress levels. Sexual dysfunction in people with diabetes has a significant impact on sexual self-concept, which includes feelings, views, and beliefs about sexual relationships. Conclusion: There hasn't been any specific research conducted on diabetic patients concerning the correlation between sexual dysfunction and sexual self-concept, highlighting the need for dedicated studies to address this association and raise awareness.